2020
DOI: 10.1080/15384101.2020.1733750
|View full text |Cite
|
Sign up to set email alerts
|

Reticulocalbin-1 knockdown increases the sensitivity of cells to Adriamycin in nasopharyngeal carcinoma and promotes endoplasmic reticulum stress-induced cell apoptosis

Abstract: 2020) Reticulocalbin-1 knockdown increases the sensitivity of cells to Adriamycin in nasopharyngeal carcinoma and promotes endoplasmic reticulum stress-induced cell apoptosis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
(35 reference statements)
1
20
0
Order By: Relevance
“…Our current data where knockdown of RCN1 led to enhanced ATF6 activity and over-expression of RCN1 mediated reduced ATF6 activity in cells when challenged with ER stress inducers is consistent with other reports. Similar to our findings, Huang et al, showed that knockdown of RCN1 enhanced the expression of ER stress markers GRP78, CHOP, Herp, Erdj4, ATF4 and EDEM1 and promoted apoptosis in nasopharyngeal carcinoma cells when challenged with the chemotherapeutic adriamycin [ 40 ]. Our current data also showed that RCN1 knockdown leads to enhanced phosphorylation of EIF2α, increased expression of ATF4 and enhanced activity of NRF2, members of another UPR pathway PERK-EIF2α-ATF4 that is divergent to the ATF6 pathway.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our current data where knockdown of RCN1 led to enhanced ATF6 activity and over-expression of RCN1 mediated reduced ATF6 activity in cells when challenged with ER stress inducers is consistent with other reports. Similar to our findings, Huang et al, showed that knockdown of RCN1 enhanced the expression of ER stress markers GRP78, CHOP, Herp, Erdj4, ATF4 and EDEM1 and promoted apoptosis in nasopharyngeal carcinoma cells when challenged with the chemotherapeutic adriamycin [ 40 ]. Our current data also showed that RCN1 knockdown leads to enhanced phosphorylation of EIF2α, increased expression of ATF4 and enhanced activity of NRF2, members of another UPR pathway PERK-EIF2α-ATF4 that is divergent to the ATF6 pathway.…”
Section: Discussionsupporting
confidence: 91%
“…Previous findings have demonstrated that the expression of the ER-localized, calcium binding protein RCN1 correlates with progression of breast, liver, kidney, lung, prostate and colorectal cancer [ 19 , 20 , 21 , 37 , 38 , 39 ] and may play an important role in mediating resistance to treatment in uterine and nasopharyngeal carcinoma [ 40 ]. However, it is unclear as to which receptor tyrosine kinases regulate RCN1 expression and whether RCN1 plays a role in glioblastoma progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RCN1 overexpression has been identified in various tumors, including liver, lung, breast, colorectal, prostate, and nasopharyngeal cancers [14][15][16][17][18][19][20]. In particular, RCN1 was implicated in the regulation of drug resistance, and RCN1 knockdown was found to reduce the resistance of nasopharyngeal carcinoma (NPC) cells/ tissues to doxorubicin, promoting NPC cell death [21]. RCN1 was also found to be upregulated in doxorubicin-resistant uterine cancer [22].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it was revealed that the ER stress-related genes-based risk model can serve as a prognostic factor to predict the outcome for patients and be correlated with immune and inflammation responses in glioma ( Zhang et al, 2021 ). Among these genes, RCN1, as an ER-resident calcium-binding protein, is verified as one of ER stress-related genes, of which the depletion causes the ER stress-induced cells’ apoptosis in various cancers ( Huang et al, 2020 ; Liu et al, 2018 ; Xu et al, 2017 ). In the early study, it was demonstrated that RCN1 was identified as a genuine phagocytosis ligand to stimulate microglial phagocytosis of apoptotic neurons that were subsequently targeted by phagosomes ( Ding et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%